2010
DOI: 10.3324/haematol.2010.027821
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine sensitizes CD40 ligand-protected chronic lymphocytic leukemia cells to bezafibrate- and medroxyprogesterone acetate-induced apoptosis but dasatanib does not overcome reported CD40-mediated drug resistance

Abstract: BackgroundTumor cells in chronic lymphocytic leukemia accumulate in the periphery through the proliferation of a minority of cells in lymph nodes. The proliferative and survival signals in these proliferation centers include interactions with T lymphocytes expressing CD40 ligand. We have demonstrated that the low toxicity combination of bezafibrate and medroxyprogesterone acetate induces mitochondrial superoxide-mediated apoptosis of non-CD40-liganded cells but not of cells exposed to CD40 ligand. Here, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…The most recent investigations have confirmed previous knowledge that MPA provokes apoptotic changes of T lymphocytes in the lymph nodes [18]. Despite multiple contradictory experimental studies, clinical observations suggest that MPA inhibits CD8 + T cell viral specific effector function and induces herpes simplex virus type 1 reactivation.…”
Section: Discussionsupporting
confidence: 67%
“…The most recent investigations have confirmed previous knowledge that MPA provokes apoptotic changes of T lymphocytes in the lymph nodes [18]. Despite multiple contradictory experimental studies, clinical observations suggest that MPA inhibits CD8 + T cell viral specific effector function and induces herpes simplex virus type 1 reactivation.…”
Section: Discussionsupporting
confidence: 67%
“…For the majority of samples this was unlikely to be a factor, owing to the high proportion of B cells present. However, to address this, samples where B cell proportions were lower were co-stained with anti-CD 19 along with Previously we have shown that the anti-leukemic activity of BEZ and MPA involves deregulation of mitochondrial func tion [27,30]; in particular in CLL we observed that the gen eration of MSO [25,27] was central to the apoptotic action of the drugs. In contrast the anti-leukemic action of BEZ, MPA and BEZ + MPA on proliferation occurred without generat ing MSO [5].…”
Section: Impact Of Cd40lon B-nhl and Effects Of Bezand Mpamentioning
confidence: 94%
“…Patients had p ro vided informed written consent for the study, which had received local ethical approval. Primary m ononuclear cells were prepared using Ficoll Paque-Plus (Anachem) as previously described [25], …”
Section: Patients and Donorsmentioning
confidence: 99%
“…Most notably, several Amaryllidaceae alkaloids are being evaluated as anti-cancer drugs [12]. Lycorine is a powerful inhibitor of ascorbic acid biosynthesis, and also a powerful inhibitor of cell growth and cell division, including antitumor activity in animal and human cell lines [58,59]. Other alkaloids of this type, such as caranine, galanthine, pseudolycorine and 2- O -acetylpseudolycorine, are also active against a variety of tumour cells.…”
Section: The Amaryllidaceae Family and Their Medicinal Alkaloidsmentioning
confidence: 99%